Controlled radical polymerization of vinyl ketones using visible light. Issue 21 (9th May 2017) - Lee, In-Hwan; Discekici, Emre H.; Anastasaki, Athina; de Alaniz, Javier Read; Hawker, Craig J.
Abstract : Herein we report the photoinduced electron transfer–reversible addition–fragmentation chain transfer (PET-RAFT) polymerization of a range of vinyl ketone monomers including methyl, ethyl and phenyl derivatives, using Eosin Y as an organic photoredox catalyst and visible light. Abstract : Herein we report the photoinduced electron transfer–reversible addition–fragmentation chain transfer (PET-RAFT) polymerization of a range of vinyl ketone monomers including methyl, ethyl and phenyl derivatives, using Eosin Y as an organic photoredox catalyst and visible light. The protocol is amenable to a range of conditions and facilitates controlled polymerization in the presence of air and even in the absence of catalyst. This approach is versatile and scalable as demonstrated by the multi-gram scale synthesis of poly(vinyl ketones) with increased polymerization rates being achieved upon the addition of triethylamine as a reducing agent. High chain-end fidelity was demonstrated by ESI-MS and 1 H NMR with successful chain extension yielding a library of novel diblock copolymers.